A taxonomic bibliography of the South American snakes of the Crotalus durissus complex (Serpentes, Viperidae) - Paulo E. Vanzolini (Anais da Academia Brasileira de Ciências, 2002)
A survey is made of the taxonomic literature on South American rattlesnakes (genus Crotalus, familyViperidae).Two main areas are emphasized: the attribution of the names proposed in the eighteenth century byLinnaeus and Laurenti, and the current scheme of division in subspecies.The attribution of names is examined based on the original descriptions and on relevant previous and contemporaryliterature. The presently adopted scheme, proposed by Klauber (1941, 1972) is found not entirelysatisfactory, but reasonable enough besides being hallowed by use.The scheme of geographical differentiation, intrinsically important and with broad practical implications(differentiation of the venom) is found to be the culmination of a long series of deficient analyses, and inurgent need of proper investigation.